The KLASIFIKASI BAHAN BERBAHAYA DAN BERACUN DI LABORATORIUM X DENGAN MENGGUNAKAN HAZMAT TOOL : KLASIFIKASI BAHAN BERBAHAYA DAN BERACUN DI LABORATORIUM X DENGAN MENGGUNAKAN HAZMAT TOOL - Novita Lizza Anggraini; Mayati Isabella; Nor Halidah; Ayumi Devidhavyasa; Christian Eben Eliezer Siahaan (EDUPEDIA Publisher, 2023)
Abstract: Hazardous and toxic materials (B3) are materials that can cause harm to living organisms, materials, buildings, or the environment due to explosion or fire hazard, corrosion, poisoning for organisms, as well as devastating consequences. The method for carrying out B3 classification is by using the Hazmat Tool. Before using the Hazmat Tool, an observation was made to find out the chemicals in Laboratory X. Based on the observations, a list of the chemicals used was obtained, then a classification was carried out to determine the storage of chemicals and after carrying out the design requirements for storing chemicals in prevent potential hazards of chemicals in Laboratory X. The classification of these chemicals is expected to increase institutional and laboratory staff knowledge regarding the importance of knowing how to store chemicals in the workplace. Keywords: Classification of chemicals, B3, Laboratory